The Measurement of the Utilisation Efficiency of External Debt Funds and Its Influencing Factors. (14th July 2015) - Yang, Yun; Chen, Leyi; Huang, Qingqing
<x xml:space="preserve">Abstract</x> This paper uses stochastic frontier analysis to measure the utilisation efficiency of external debt funds, and identifies what factors actually influence the utilisation efficiency of external debt funds. Measurements show that in both developing and developed countries, the utilisation efficiency of external debt funds shows a downward trend; this downward trend is more obvious in developed countries. Empirical analysis found that the trade deficit rate, the trade openness, the ratio of fiscal revenue to gross domestic product (GDP), and the inflation rate have a significant negative effect on the utilisation efficiency of external debt funds. The ratio of money and quasi money (M2) to GDP, the ratio of the population aged 15–65 to total population, the ratio of industry value‐added to GDP, and the investment growth rate have a significant positive effect on the utilisation efficiency of external debt funds. Furthermore, under the condition of high ratio of the population aged 15–65 to total population, an increase in the ratio of the population aged 15–65 to total population will have a larger effect on improving the utilisation efficiency of external debt funds. Under the condition of high trade deficit rate, an increase in trade deficit rate will have a bigger effect on decreasing the utilisation efficiency of external debt funds.